Proteomic analysis of meropenem-induced outer membrane vesicles released by carbapenem-resistant Klebsiella pneumoniae - Fangfang Fan; Guangzhang Chen; Siqian Deng; Li Wei (Microbiology Spectrum, 2024)
ABSTRACTCarbapenem-resistant Klebsiella pneumoniae (CRKP) is an important multidrug resistance (MDR) pathogen that threatens human health and is the main source of hospital-acquired infection. Outer membrane vesicles (OMVs) are extracellular vesicles derived from Gram-negative bacteria and contain materials involved in bacterial survival and pathogenesis. They also contribute to cellular communication to nearby or distant recipient cells and influence their functions and phenotypes. In this study, we sought to understand the mechanism of bacterial response to meropenem pressure and explore the relationship between pathogenic proteins and the high pathogenicity of bacteria. We performed whole-genome PacBio sequencing on a clinical CRKP strain, and its OMVs were characterized using nanoparticle tracking analysis, transmission electron microscopy, and proteomic analysis. Thousands of vesicle proteins have been identified in mass spectrometry-based high-throughput proteomics analyses of K. pneumoniae OMVs. Protein functionality analysis showed that the OMVs were predominantly involved in metabolic, intracellular compartments, nucleic acid binding, survival, defense, and antibiotic resistance, such as Chromosome partition protein MukB, 3-methyl-2-oxobutanoate hydroxymethyltransferase, methionine—tRNA ligase, Heat shock protein 60 family chaperone GroEL, and Gamma-glutamyl phosphate reductase. Additionally, a protein-protein interaction network demonstrated that OMVs from meropenem-treated K. pneumoniae showed the highest connectivity in DNA polymerase I, phenylalanine–tRNA ligase beta subunit, DNA-directed RNA polymerase subunit beta, methionine–tRNA ligase, DNA-directed RNA polymerase subunit beta, and DNA-directed RNA polymerase subunit alpha. The OMVs proteome expression profile indicates increased secretion of stress proteins released from meropenem-treated K. pneumoniae, which provides clues for revealing the biogenesis and pathophysiological functions of Gram-negative bacteria OMVs. The significant differentially expressed proteins identified in this study are of great significance for exploring effective control strategies for CRKP infection.IMPORTANCEMeropenem is one of the main antibiotics used in the clinical treatment of carbapenem-resistant Klebsiella pneumoniae (CRKP). This study demonstrated that some important metabolic changes occurred in meropenem-induced CRKP-outer membrane vesicles (OMVs), The OMVs proteome expression profile indicates increased secretion of stress proteins released from meropenem-induced Klebsiella pneumoniae. Furthermore, this is the ﬁrst study to discuss the protein-protein interaction network of the OMVs released by CRKP, especially under antibiotic stress.